The phenology of migration in an unpredictable world. Issue 1 (21st January 2019) - Schindler, Daniel E.
Abstract: In Focus: Freshwater, C., Trudel, M., Beacham, T. D., Gauthier, S., Johnson, S. C., Neville, C. &Juanes, F. (2016 )Individual variation, population‐specific migration behaviours and stochastic processes shape marine migration phenologies .Journal of Animal Ecology, 88, 67 –78 .https://doi.org/10.1111/1365-2656.12852 Pacific salmon undertake arduous and risky migrations from their freshwater nursery grounds to the coastal ocean, northwards to their feeding grounds, and then back to their freshwater natal habitats to spawn. Understanding the phenology of such migrations has largely been viewed through the lens of microevolution producing optimal strategies that reflect local selection pressures; less emphasis has been placed on quantifying how variation in migration patterns can spread the risks associated with life in variable and unpredictable ecosystems. In this issue, Freshwater et al. use the information contained in ear stones (otoliths) and DNA of migrating juvenile sockeye salmon from the Fraser River of western Canada to quantify variation in the timing of their marine migrations. Not only were there population‐specific differences in migration phenology of fish from the same river, but there was substantial variation among individuals from specific populations. These patterns also varied from year to year. Data like these emphasize the risks involved in such migrations and suggest that variation in key migration traits are maintained because of the inherent unpredictability of ecosystems. Management and conservation efforts would be well‐served to consider actions that maintain such ecological variation to facilitate meta‐population persistence in a rapidly changing world. Abstract : This In Focus argues that the considerable variation in the phenology of migration by juvenile salmon is a reflection of the highly variable and unpredictable world they live in. Management should seek to maintain this variation.